Educación financiera y su influencia en la toma de decisiones en los estudiantes del 1er nivel de la escuela de administración FACEN-UNAP año 2020 - Muñoz Ramirez, Marilin Estefania (2021)
The objective of this tesis is to determine the relationship that exists between financial education and decision-making in students of the 1st leve lof the Facen-Unap school of administration in 2020. The type design that was used is quantitative, not experimental, since the variables are not manipulated, relying on the observation of phenomena as they occur in their natural environment. The study population is made up of 60 students from the 1st leve lof the management school. The techique used is the survey applied to said university students, which was very helpful in identifying the existing problems. It was concluded that Financial Education signicantly influences the decision-making of students of the 1st leve lof the Facen-Unap School of Administration in 2020